Implicancias jurídicas del modelo social de discapacidad en la imputabilidad penal - Torres Flor, Analucía (2024)
The entry into force of Legislative Decree No. 1384 meant that Peru incorporated into its legislation on legal capacity the paradigm of the Social Model of Disability contained in the Convention on the Rights of Persons with Disabilities (2006). This has meant a resounding change in the understanding of the notion of capacity and the existing interaction between the legal system and any person who presents psychosocial, intellectual and/or cognitive deficiencies, since now what was initially an impediment to the exercise of their rights and obligations is no longer an impediment and it is assumed that every person enjoys full legal capacity to deploy their legal sphere. Now, considering that the Law is presented as a normative system that responds to criteria of logic and internal coherence and that its considerations are based on a common factor such as the person and his behavior, the following question arises: what are the implications that this change causes in the legal treatment of the capacity to be subject to criminal charges? From this perspective, we analyze how this new conception of capacity would operate in the field of criminal law, mainly that referring to the notions of imputability and culpability. This responds to the fact that these categories are also structured on the notion of capacity as aptitude to be motivated in accordance with the norm or to infringe it and, thus, be considered responsible for the typical wrongdoing and deserving of punishment. In this line, we consider that the Social Model of Disability would imply that the bases of the sanction in the criminal field, contained in the mentioned categories, are also reformulated, since the notion of capacity is a unanimous element to the legal reasoning that is based on the logic of the duty that every person has to adapt his conduct to the Law, which cannot be considered in an abstract way by the legal system, as the legislation inspired by the mentioned model would do.